Nature and the Historization of History - a Commentary - Eriksen, Anne (Tidsskrift for kulturforskning, 2008)
In his text, Kragh gives a brief but very informative overview of the idea that nature itself is historical, i.e. subject to change over time. He includes a discussion on whether even the natural laws themselves may be changing in this way, and ends by asking if nature is "truly historical" in the same way as human societies are. He answers in the negative. One of the arguments he uses is that while a historian can think back in time and identify with the historical actors, the scientist cannot in the same way imagine being a dinosaur or a molecule.